Pengetahuan dan Sikap Ibu Primigravida dengan Persiapan Persalinan - Anita Tryxie Mehengkeng; Yuke T. Darado; Cut Mutiya Bunsal (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Labor preparation aims to prepare for the needs during pregnancy and labor. The close relationship between maternal knowledge and attiudes towards childbirth is very important to improve the preparation of primigravida mothers to undergo the birth process smoothly and safely. The purpose of the study was to determine the relationship between knowledge and attitudes of primigravida mothers with labor preparation in the manganitu Health Center working area. The study was conducted using purposive sampling method. Data collection was done by means of a questionnaire. Furthermore, the collected data were processed using the SPSS computer program to be analyzed with uni statistics and chi square test. The result of the study there is a relationship between knowledge and labor preparation p value=<.001 where the p value is smaller yhan the value of a=0.05 and there is a relationship between attitude and labor preparation p value=<.001 where the p value is smaller than the value af a=0.05. The conclusion of this study is that there is relationship between knowledge and attitude of primigravida mothers with labor preparation in the Manganitu Health Center working area